Impact of vacancies in halide perovskites for batteries and supercapacitors - Choon, Si Lin; Lim, Hong Ngee (Elsevier Ltd, 2024)
The advancement and evolution of halide perovskites have been witnessed by wide areas of researchers owing to their distinctive and adaptable properties. Promising features in photovoltaics and optoelectronics empower the continual research of halide perovskites in the related field. The emergence of energy storage devices based on halide perovskites began recently and is still in phase of infancy. Vacancies, one of the common structural defects in halide perovskites are potentially to promote the growth of halide perovskites in the energy storage field, by facilitating ionic migration, ionic conductivity, and surface area. Notably, vacancies are playing the villain role in photovoltaics most of the time. Herein, the overview of perovskite structures and the essential vacancies in different perovskites are reviewed. The synthesis techniques for the halide perovskites with vacancies are summarized. The influence of halide perovskite vacancies on energy storage devices' performance and the methods to detect the vacancies-induced effects are discussed. Lastly, the challenges and perspectives on future directions of utilizing halide perovskites with vacancies in energy storage devices are presented.